Intention Quality Model For E-Commerce Based On Islamic Values Among Muslim Students - Abdalslam S Imhmed Mohmed
E-commerce is the process of sharing business information, maintaining a business relationship and performing business transactions via computer networks. It provides many advantages such as sharing and exchanging information, building a relationship and conducting business transactions by organisations using internet technologies. Due to fraudulent or misuse of personal information, online purchase intention and demand for secured online transaction has been declined. Not only that developing online trust and coping with the risks of online transactions are major challenges of small and medium enterprises (SMEs). As such, this research investigates customer's intention to purchase online from SMEs based on Islamic Value. Quantitative approach was used for data collection and data analysis. Data was collected by using survey and the semi-structured interview. The respondents for the survey are the consumers who are having experience of purchasing through e-commerce. The quantitative data were analysed by using structural equation modelling (SEM) technique. The findings revealed that beta coefficient of information quality and behavioral attitude had a high influence on the intention to purchase through e-commerce by 0.378 and 0.351 respectively. With the significant standardized regression weights of all the constructs and items, the overall squared multiple correlations were found to be 0.72 (72%) which is considered as very strong and significant finding of the study. This research provides a guideline to the online sellers especially the SMEs on the important factors that they need to consider when designing and preparing their website. All these factors may increase the actual purchase online. Nevertheless, the result may be different due to the variety of business model.